Peningkatan Hasil Belajar IPA dengan Menggunakan Model Cooperative Picture And Picture di Kelas IV Siswa SDN 007 Muara Jalai Kampar - Suci Triana; kasman Edi Putra (Jurnal Pendidikan Tuntas, 2023)
This researchis based on the low learning outcomes of studens in IPA subjects especially on the material changes in the appearance of aerth. On solustion to overcome this problem is to use Cooperative learning model of Picture And Picture type. Thus the purpose of this study is to describe learning outcomes on science learning through application model of Cooperative learning Picture And Picture type in fourth grede students of elementary school. This research was conductted twice and eath cyle was held 2 times. This researchis implemented at SDN 007 Muara Jalai with research subject of research is class IV SDN. Data collection in this study using documentation, test , and observation techniques. Improvement of student’s learning outcomes learning changes in the appearance of the earth from before the completed student action overall 10 students or with a percentage of 43,47%, cyle 1 students who completed overall increased 15 percentage 65,21%, and in cyle II the complete students or with percentage 86,95%. And average students score increased from before 69,82%, cyle I with average 71,30% increased to 78,04% in cyle II. So, learning Perubahan Kenampakan Bumi earth with the model of Cooperative learning type of Picture And Picture can improve student learning outcomes class IV.